Using an Ontology-based Approach for Integrating Applications to support Software Processes - Renault, Laylla D. C.; Barcellos, Monalessa Perini; Falbo, Ricardo de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software organizations use several applications to support their software processes. To properly support the software processes, applications should be integrated at different layers (data, service, and process). Moreover, the integration should cover semantic aspects. Therefore, an approach that provides guidelines on how to perform integration at different layers addressing semantic aspects can be helpful. This paper presents an extension of the Ontology-based Approach for Semantic Integration (OBA-SI), focusing on semantic integration at process layer. This extension establishes relationships between integration at data, service and process layers, and uses task ontologies and a process ontology to guide integration at process layer. It was used to provide an integrated solution involving applications supporting the Issue Management and Software Configuration Management processes.